Design of a new ultra wideband planar antenna for wireless communication systems. Issue 6 (27th March 2013) - Bassouh, M.; Aznabet, M.; Meloui, M.; Mrabet, O. El; Falcone, F.; Khalladi, M.
Abstract A new planar circular monopole antenna for ultra wideband (UWB) applications is presented. To achieve UWB characteristics, the proposed antenna is constructed by embedding the slot on the partial ground plane. The proposed antenna has been successfully simulated and measured. Experimental results indicate that the proposed antenna yields an impedance bandwidth of 2.3 up to 13 GHz with VSWR < 2, which makes it suitable to operate not only for UWB bandwidth but also it can be used also for WLAN application. © 2013 Wiley Periodicals, Inc. Microwave Opt Technol Lett 55:1335–1338, 2013; View this article online at wileyonlinelibrary.com. DOI 10.1002/mop.27584